2007
DOI: 10.1007/s00436-007-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein alterations in dogs naturally infected with Toxoplasma gondii

Abstract: We conducted this study to describe the serum electrophoretic pattern in dogs associated with the infection of Toxoplasma gondii (T. gondii). The serum protein pattern of 25 dogs with confirmed T. gondii infection and 15 clinically healthy dogs were evaluated using native polyacrylamide gel electrophoresis. Albumin, alpha-1 globulin, alpha-2 globulin, beta globulin, and gamma globulin bands were seen from the serum electrophoresis of infected and healthy dogs. Compared to the control group, significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
4
3
0
Order By: Relevance
“…The significantly elevated serum activities of aminotransferases in the serologically positive cases of toxoplasmosis in this study are in agreement with several studies (28)(29)(30)(31) . These results also agree with the studies performed on experimental animals (32,(35)(36)(37) .…”
Section: Discussionsupporting
confidence: 92%
“…The significantly elevated serum activities of aminotransferases in the serologically positive cases of toxoplasmosis in this study are in agreement with several studies (28)(29)(30)(31) . These results also agree with the studies performed on experimental animals (32,(35)(36)(37) .…”
Section: Discussionsupporting
confidence: 92%
“…We found that plasma AST and ALT activities were increased in T. gondii-infected gerbils, consistent with previous studies conducted on rats (14,41). Several studies have also demonstrated increased serum AST and ALT activities in T. gondiiinfected mice, dogs and goats (6,20,51). Increased plasma AST and ALT activities reflects impairment of the liver.…”
Section: Discussionsupporting
confidence: 80%
“…Boothroyd et al (14) observed that toxoplasmosis led to an increase in serum protein and globulin concentrations and a decrease in serum albumin concentrations during the acute stage. Yarim et al (51) reported that T. gondii infection causes hypoalbuminemia in dogs. Our results are consistent with those of previous studies (6,14,51), except for the globulin and total protein concentrations measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxoplasmosis causes liver pathologies [ 27 ], and the significant agreement of serologically positive cases with elevated plasma AST and ALT has been reported [ 28 ]. A decrease in GSH activity was detected, while an increase of MDA was observed in T. gondii -infected patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%